2016
DOI: 10.5038/2375-0901.19.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Use a Public Bicycle System: An Example in Nanjing City

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Travel cost, comfort, age and gender also affect the choice for PBSS. A study (Feng and Li 2016) for Nanjing city (China) concluded that socio-economic factors (such as gender, employment status and car ownership) are more important than journey restriction variables in defining the user willingness to use PBSS. Another recent study (Campbell et al 2016) used a stated preference data from Beijing (China) for determining user's preferences for conventional and electric bikes within a PBSS.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Travel cost, comfort, age and gender also affect the choice for PBSS. A study (Feng and Li 2016) for Nanjing city (China) concluded that socio-economic factors (such as gender, employment status and car ownership) are more important than journey restriction variables in defining the user willingness to use PBSS. Another recent study (Campbell et al 2016) used a stated preference data from Beijing (China) for determining user's preferences for conventional and electric bikes within a PBSS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies investigate user preferences for the citywide infrastructure of PBSS installed in large cities (Bachand-Marleau et al 2012;Feng and Li 2016), where PBSS infrastructure such as the number of bicycles and distance between the docking stations have been found as the major determinants of use of PBSS. However, limited studies exist that focused on determining the users preferences for use of PBSS for their inter-modal trip, especially with rail.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we addressed the necessity for research into the nonlinear relationship between the subjective and objective dimensions of the cycling environment and its impact on cycling distance. Concerning objective factors, there is a widespread belief that socio-economic indicators are closely linked to cycling distance (Feng & Li, 2016). However, in special situations such as the pandemic period, this correlation may not be significant (Schaefer et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mainstream literature indicates that objective attributes like land-use elements and street design in the cycling environment significantly impact riding distance (Chen et al, 2022;Feng & Li, 2016;Ferenchak & Marshall, 2021;Kim et al, 2012;Ospina et al, 2020;Wang et al, 2018;Wei & Zhu, 2023). However, most studies predicting riding distance typically concentrate solely on objective cycling environments.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the BSP consumer profile entails identifying socio-demographic parameters [73]. Gender, age, education, money, and car ownership affect bike-sharing demand.…”
Section: Socio-demographic Impact Factorsmentioning
confidence: 99%